2020
DOI: 10.3390/ijerph17239145
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Websites’ Digital Communication Strategies in Latin American Hospitals During the COVID-19 Pandemic

Abstract: Since the advent of the Internet, websites have become the nerve center of the digital ecosystems of media, companies and all kinds of institutions. Currently, the impact of the global coronavirus pandemic has placed healthcare issues at the center of social debate, including hospitals and their websites as digital sources of trustworthy information. COVID-19 has intensified the need for quality information and the legitimacy of sources fighting the infodemic situation. In this regard hospitals become essentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 29 publications
0
4
0
2
Order By: Relevance
“…Regarding the role of information systems in COVID-19, this study implies that institutional environments should be considered when initiating digital health related policies or projects. After tracking websites’ digital communication strategies in Latin America hospitals during the COVID-19 pandemic, Tejedor et al [ 147 ] suggested that digital media could constitute legitimate resources for healthcare information consumption, so their accuracy and proper development seem to be significant to becoming a genuine source. In addition, after studying Electronic Health Record (EHR), Beglaryan et al [ 52 ] indicated that institutional factors as well as personal benefits at the micro level should be considered.…”
Section: Discussion and Implicationmentioning
confidence: 99%
“…Regarding the role of information systems in COVID-19, this study implies that institutional environments should be considered when initiating digital health related policies or projects. After tracking websites’ digital communication strategies in Latin America hospitals during the COVID-19 pandemic, Tejedor et al [ 147 ] suggested that digital media could constitute legitimate resources for healthcare information consumption, so their accuracy and proper development seem to be significant to becoming a genuine source. In addition, after studying Electronic Health Record (EHR), Beglaryan et al [ 52 ] indicated that institutional factors as well as personal benefits at the micro level should be considered.…”
Section: Discussion and Implicationmentioning
confidence: 99%
“…Regarding the role of information systems in COVID-19, this study implies that institutional environments should be considered when initiating digital health related policies or projects. After tracking websites' digital communication strategies in Latin America hospitals during the COVID-19 pandemic, Tejedor et al [147] suggested that digital media could constitute legitimate resources for healthcare information consumption, so their accuracy and proper development seem to be significant to becoming a genuine source. In addition, after studying Electronic Health Record (EHR), Beglaryan et al [52] indicated that institutional factors as well as personal benefits at the micro level should be considered.…”
Section: Discussing the Main Resultsmentioning
confidence: 99%
“…YouTube ha sido descrito como una cultura participativa intermediaria, en la que tanto las organizaciones comerciales como los aficionados producen contenidos simultáneamente, por lo que están constantemente negociando y construyendo sus relaciones con sus espectadores (Harris et al, 2020). Estas particularidades añaden un interés destacado a esta plataforma, cuyo estudio se enmarca en la relevancia de los trabajos sobre el uso de herramientas digitales en al ámbito de la salud (Tejedor et al, 2020).…”
Section: Youtube Y La Divulgación De Contenidos De Saludunclassified